2005
DOI: 10.1021/ie0502180
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of a Trickle Bed and a Monolith for Hydrogenation of Pyrolysis Gasoline

Abstract: The applicability of a monolith system to a retrofit application for the hydrogenation of pyrolysis gasoline (Pygas) is evaluated. A direct comparison between a trickle bed (extruded trilobe) and a washcoated monolith is made using a simulated model Pygas mixture. Comparable nickel impregnated onto alumina catalysts (trilobe and monolith) are evaluated in a laboratory recycle reactor operating under the same industrially relevant conditions of temperature, pressure, and liquid/gas flow rate. The inferred flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…For an industrial‐scale deployment of monolith reactors, the performance of the monolith reactor and its comparison with TBR performance should be known. Such comparative studies have been reported by various authors . It should be noted that compared to monolith reactors, TBR have been well studied.…”
Section: Introductionmentioning
confidence: 66%
“…For an industrial‐scale deployment of monolith reactors, the performance of the monolith reactor and its comparison with TBR performance should be known. Such comparative studies have been reported by various authors . It should be noted that compared to monolith reactors, TBR have been well studied.…”
Section: Introductionmentioning
confidence: 66%
“…This is confirmed when the trial data are analyzed, with the results shown in Table 2. It can be seen that the solubility of the gas RDT k L a = 0.0171 × (N/1000) 6.05 e 0.38 × 10 −6 P + 0.00525…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This often manifests as an apparent zero order kinetics with respect to time or conversion of other reactants, while at constant pressure. If C H 2 varies between reactors, for example, because of higher k L a in the laboratory than on plants, then both homogeneous concentration and heterogeneous catalyst surface coverage can also vary, potentially leading to alternate reaction pathways and selectivity to the wrong product. For most processes, this would be highly problematic; for the pharmaceutical industry, it can be disastrous and could have a lasting impact on human health.…”
Section: Introductionmentioning
confidence: 99%
“…The TBR was operated either under semibatch mode where all the liquid flow was circulated back into the reactor by the metering pump while the gas was vented or in continuous mode, where a portion of the liquid feed was removed from the reactor while 99.75% of the liquid was recycled. This protocol has been described by the groups of Hickman 20 and Pollington 21 to ensure complete wetting of the catalyst bed and minimisation of external mass transfer, thereby allowing reliable measurement of a rate of reaction. The inlet and outlet flow of the liquid feed were both set to 1 mL min −1 .…”
Section: Methodsmentioning
confidence: 99%